What is digital identity? - Olivier Ertzscheid (OpenEdition Press, 2016)
The question of digital identity and e-reputation is central in today's Internet ecosystem, both in terms of individual and collective use. This book is an accessible guide to cutting-edge research on the subject and provides an overview of the fundamental issues that individuals need to master in order to retain control over their or their organization's online presence. This is a book for readers who wish to discover more about this rich and complex issue, as well as for businesses, organi...